IMPROVING TRADITIONAL MARKET CUSTOMER LOYALTY (REVISIT CONSUMER BEHAVIOUR MODEL USING CONSUMER EXPERIENCE) - Ayuni, Risca Fitri; Hussein, Ananda Sabil; Hapsari, Radhita (Accounting Department,, 2018)
The main purpose of this study is to explore any dimension from traditional market consumer’s experiences that could affect their behaviour. The variables included in this study are experience quality, perceived value, visitor’s satisfaction, and customer loyalty. This study divided into two phases: exploring any indicators that construct the experience quality of traditional market’s customer using Exploratory Factor Analysis, and analysing the relationship between the variables on the model. In the first phase, the data was collected by doing a Focus Discussion Group that consist of six to nine traditional market’s customers. The data for the second phase was collected by questionnaire on 250 traditional market’s customer. This study found there are seven indicators that could construct the experience quality of traditional market’s customer, however the experience quality is found to have no significant effect toward customer loyalty. In addition perceived value and visitor’s satisfaction is proved to have significant effect toward customer loyalty, thus these two variables could fully mediate the relationship between experience quality and customer loyalty.